PERANAN SULFUR DIOKSIDA PADA PEMBENTUKAN KOROSI LOGAM DAN IMPLIKASINYA BAGI KESEHATAN MANUSIA DI GUNUNG LUMPUR, DESA KUWU, KECAMATAN KRADENAN, KABUPATEN GROBOGAN, PROPINSI JAWA TENGAH - Arie Noor Rakhman (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
This research aims to review the existence of sulfur dioxide result of the mud volcanoes Bledug Kuwu. Research sites in the Kuwu Area, Kradenan District, Grobogan Regency, Central Java Province. Utilization of research results for the potential of sulfur dioxide’s influence for human health by identification of the nature of corrosion metal formed. The method used in the form of field and laboratory, that was performed by comparing some of physical and chemical characteristic of mud and water. The determination supported by observation the nature of corrosion metal in the field. By recognizing geology medical condition following corrosion metal identification, its obtained benefit to analyze the potential an impairment of health and directive treatment. Farther away from the center of the mud volcano, the potential of sulphur gas pollution tends to be low. Sulphur content less than 73,83 ppm to 10,90 ppm. Pollution influenced by geogen and biogen, that it was identified from the growth of vegetation and corrosive metal existence. Vegetation can live starting 200 meters from the center of the mud volcano and fertile at more than 300 meters. This were in accordance with the existence of corrosion (rusts) on metal that its more vulnerable when approaching to the center of the mud volcano. Potential an impairment of health are irritation respiratory systems, irritation of the windpipe, acute toxicity for the old man and there are had the disease chronic in cardiovascular respiratory system. Hence tourist development should be accompanied by medical equipment, awareness of the use of mask to anticipate respiratory disorders, socialozation for visitors and the community of the most sensitive due to pollutants sulfur dioxide